A Systematic Review on the Level of Digital Competence of In-Service Spanish Teachers According to the DigCompEdu Framework - Laureano Cid-Martínez; Inmaculada Aznar-Díaz; Gerardo Gómez-García; José-Antonio Martínez-Domingo (Education Sciences, 2025)
Digital training is one of the main challenges for in-service non-university teachers. In recent years, the DigCompEdu framework has gained momentum in non-university education, with several training activities taking place within this theoretical framework. This paper develops a systematic review that aims to analyze the studies that analyze the level of digital competence of in-service teachers in the different dimensions of the DIGCOMPedu framework. The PRISMA protocol for this type of study was followed and an exhaustive search was carried out in the WoS and Scopus databases, obtaining a total of seven studies (n = 7) that met the inclusion and exclusion criteria. The results of the review show an average low level in all dimensions, especially in the ability and skill of enhancing the digital competence of students. On the other hand, possible predictors of the digital competence of teachers are elucidated, among which experience and previous ICT training stand out, among others that the recruited studies show. These results could reflect the need to support training policies that promote not only instrumental training in educational technology but the importance of how to transfer this to teacher examples and didactic guidelines on how to promote digital environments conducive to developing the digital competence of their students.